2012
DOI: 10.1152/ajpregu.00275.2012
|View full text |Cite
|
Sign up to set email alerts
|

IGF-I measurement across blood, interstitial fluid, and muscle biocompartments following explosive, high-power exercise

Abstract: Insulin-like growth factor-I (IGF-I) resides across different biocompartments [blood, interstitial fluid (ISF), and muscle]. Whether circulating IGF-I responses to exercise reflect local events remains uncertain. We measured the IGF-I response to plyometric exercise across blood, ISF, and muscle biopsy from the vastus lateralis. Twenty volunteers (8 men, 12 women, 22 ± 1 yr) performed 10 sets of 10 plyometric jump repetitions at a 40% 1-repetition maximum. Blood, ISF, and muscle samples were taken pre- and pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 39 publications
3
19
1
Order By: Relevance
“…There is no evidence, however, that the hepatic-derived IGF-1, mediated through release via the GH-IGF-1 axis, and measured in circulation is related to levels in the muscle. In fact, a recent study by Nindl and colleagues showed that there was no relationship between IGF-1 measured in the blood and IGF-1 protein content within the muscle [41]. The lack of correlation between muscle hypertrophy and IGF-1 measured in the blood observed in this study is not surprising in light of the work by Nindl et al showing no relationship between IGF-1 protein in the muscle or interstitial space and IGF-1 in the blood [41].…”
Section: Discussionmentioning
confidence: 99%
“…There is no evidence, however, that the hepatic-derived IGF-1, mediated through release via the GH-IGF-1 axis, and measured in circulation is related to levels in the muscle. In fact, a recent study by Nindl and colleagues showed that there was no relationship between IGF-1 measured in the blood and IGF-1 protein content within the muscle [41]. The lack of correlation between muscle hypertrophy and IGF-1 measured in the blood observed in this study is not surprising in light of the work by Nindl et al showing no relationship between IGF-1 protein in the muscle or interstitial space and IGF-1 in the blood [41].…”
Section: Discussionmentioning
confidence: 99%
“…Of the two, IGF-I has been most extensively studied and is secreted as it is produced by the liver in response to GH stimulation. Only 2% of IGF-I circulates in its free form; most circulates as a binary (20-25%) or ternary complex (∼75%) (146)(147)(148)(149). In its binary form, IGF-I circulates with one of seven binding proteins whereas in its ternary form, IGF-I circulates with IGFBP-3 and its acid labile subunit (ALS).…”
Section: Current Perspectives On Igf-i and Physiological Adaptations mentioning
confidence: 99%
“…Exercise duration and total work also may impact IGFBP-1 changes but it was not see that the modality had as much impact on the response patterns. With the novel technique of microdialysis to measure IGF-I in the interstitial fluid, Nindl et al (149) showed total and free IGF-I and IGFBP-3 were elevated. However, IGF-I in interstitial fluid was unaltered following high-power resistance type exercise.…”
Section: Acute Responses and Chronic Adaptations Of Igfs To Resistancmentioning
confidence: 99%
“…) do not alter systemic IGF‐1), and does not reflect local IGF‐1 signalling after exercise (Nindl et al . ). Further, the activity and half‐life of systemic IGF‐1 is heavily influenced by IGF binding proteins and an acid‐labile subunit (Jones & Clemmons, ).…”
Section: Introductionmentioning
confidence: 97%
“…By contrast, exercise-induced changes in circulating IGF-1 are equivocal, with increases, decreases and no changes reported (Kraemer et al 1990(Kraemer et al , 1991(Kraemer et al , 1995. Systemic IGF-1, which is stimulated by pituitary-released GH and is primarily the result of liver secretions (IGF-1Ea isoform), is distinct from local compartments of IGF-1 (overexpression of muscle IGF-1 ( Barton-Davis et al 1998) and tendon injection of GH (Vestergaard et al 2012) do not alter systemic IGF-1), and does not reflect local IGF-1 signalling after exercise (Nindl et al 2012). Further, the activity and half-life of systemic IGF-1 is heavily influenced by IGF binding proteins and an acid-labile subunit (Jones & Clemmons, 1995).…”
Section: Introductionmentioning
confidence: 99%